2015
DOI: 10.1080/15421406.2014.953748
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Photo Actuated Bulk Nanocomposite with Nematic Liquid Crystalline Elastomer Matrix

Abstract: Liquid crystal elastomers (LCEs) are excellent actuator materials. However, current LCE materials are generally made in the forms with thin thickness, such as films or fibers, which have limitations in forming actuators. We have developed a bulk LCE material with the three-dimensional elastic skeleton network of polyurethane and the matrix of nematic LCE incorporating single-wall carbon nanotubes (SWCNTs). This LCE nanocomposite bulk (LCENB) exhibited sensitive and reversible photo actuation. It could evenly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 41 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…While the research and development on light-driven liquid crystalline polymers and elastomers are continuing, there is a parallel development of nanocomposites from these fascinating materials. It is worth noting that photoresponsive liquid crystalline nanoparticles have already been realized. , Carbon nanotubes, graphene derivatives, gold nanoparticles, and upconversion nanoparticles have been embedded into the liquid crystalline polymer and elastomer matrices in the hope of enhancing their existing properties or enabling new properties and phenomena. In the following, we present the recent developments in this area of LC nanaoscience.…”
Section: Light-driven Liquid Crystalline Polymers and Elastomersmentioning
confidence: 99%
“…While the research and development on light-driven liquid crystalline polymers and elastomers are continuing, there is a parallel development of nanocomposites from these fascinating materials. It is worth noting that photoresponsive liquid crystalline nanoparticles have already been realized. , Carbon nanotubes, graphene derivatives, gold nanoparticles, and upconversion nanoparticles have been embedded into the liquid crystalline polymer and elastomer matrices in the hope of enhancing their existing properties or enabling new properties and phenomena. In the following, we present the recent developments in this area of LC nanaoscience.…”
Section: Light-driven Liquid Crystalline Polymers and Elastomersmentioning
confidence: 99%
“…Such LCE materials are generally fabricated through the incorporation of light-absorbing components with LCE matrices, the light-absorbing components absorb and convert light energy into heat which then drives the deformations of LCE materials [9,32]. Carbon nanotubes [33][34][35][36][37][38][39], graphene materials [40][41][42][43], noble metallic nanoparticles [44][45][46][47][48][49][50], and conjugated polymer particles [51] have been proved to be the effective components of photothermal conversion. However, the heterogeneity because of hetero-phase structure and agglomeration of particles can hamper the performances of LCE materials.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have fabricated AZO-CLCP nanocomposites capable of photo-induced deformation upon exposure to near-infrared light or visible light by introducing upconversion nanophosphors into matrices [25,26]. Through the incorporation of polyethylene films, a poly vinyl alcohol matrix or a polyurethane network with CLCPs or LCEs, the materials obtained good forming capabilities, mechanical features and recyclable utilization [16,17,18,27,28,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) and graphene-typed materials have been widely studied for their extraordinary physical properties, such as good absorption in the visible/near-infrared region, high mechanical strengths and conductivities, etc [31]. Therefore, CNTs and graphene-typed materials have been successfully incorporated into CLCPs and LCEs to improve the materials’ mechanical properties, and their unique photo-thermal conversion effect and high thermal conductivities make them efficient nanoscale heaters to generate localized heating upon light irradiation, thereby inducing the LC-to-isotropy phase transition of matrices, and hence the reversible deformation of CLCP or LCE materials [27,28,29,30,32,33,34,35,36,37,38,39,40,41]. CNTs can obviously affect the structure and property of incorporated organic molecules by noncovalent interactions [31], it has been reported that the CNTs with aligned nanostructure could effectively orient the mesogens of CLCPs along the axis of CNTs [42].…”
Section: Introductionmentioning
confidence: 99%